Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Circularly Polarized Lasing from a Microcavity Filled with Achiral Single‐Crystalline Microribbons - Liang, Qian; Ma, Xuekai; Long, Teng; Yao, Jiannian; Liao, Qing; Fu, Hongbing (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

(Re-)inventing Biblical Traditions: The Representation of Pontius Pilate in Contemporary Historical Fiction. - Behler, Felix (Narrative Ethics and Character in the Representation of the Past in Contemporary Fiction. Organisation: Dr. Christine Berberich (University of Portsmouth), Dr. Armelle Parey (Universite de Caen Normandie).)

Monitoring Polymeric Fouling in a Continuous Reactor by Electrochemical Impedance Spectroscopy - Neßlinger, Vanessa; Rust, Sören; Atlanov, Jan; Pauer, Werner; Grundmeier, Guido (Chemie Ingenieur Technik)
Abstract Monitoring early stages of polymeric deposit formation and its prevention were studied by in‐situ electrochemical impedance spectroscopy (EIS) in a continuously operating reactor employed for polymer production. An EIS flow cell was designed and employed during the emulsion polymerization of vinyl acetate. The electrochemical analysis of the complex impedance at the solution/reactor interface allows the time‐resolved detection of film formation processes. In comparison to oxide‐covered stainless steel, an anti‐adhesive sol‐gel coated alloy showed a significant inhibition of poly(vinyl acetate) fouling. The EIS‐based approach proved to be a valuable tool for monitoring both thin barrier film performance and fouling processes under harsh process conditions.

Zwischen Angst und Vorfreude – Emotionales Erleben Lehramtsstudierender bei der Arbeit mit Eigenvideografien - Pollmeier, Pascal; Vogelsang, Christoph; Rogge, Tim
Keywords: Emotionen; Video; Eigenvideografie; Studierende; Lehramt; Praxissemester; Unterricht

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias; Kremer, H.-Hugo

Fostering Self-Regulated Entrepreneurial Learning (SREL) in Entrepreneurship Education - Fahrbach, Manuel; Jenert, Tobias; Fust, Alexander Paul; Büker, Ronja; Bellwald, Noah (Academy of Management Proceedings)

TPACK, DPACK, XY-Pack? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Das TPACK-Modell wird häufig zur Konzeptualisierung digitaler Kompetenzen in der Lehrer:innenbildung herangezogen. Es stellt die Bezüge des Lehrer:innenwissens zwischen den Dimensionen des inhaltlichen, pädagogischen und technologischen Wissens her. Wir analysieren in diesem Beitrag die Passung von TPACK zur Modellierung digitaler Kompetenzen für den Kontext der beruflichen Bildung, insb. mit Blick auf die Inhaltsdimension. Wir argumentieren, dass TPACK und solche Modelle, die sich daran anlehnen, den doppelten inhaltlichen Gegenstandsbezug der beruflichen Bildung nicht hinreichend abbilden. Darauf aufbauend diskutieren wir mögliche Weiterentwicklungen des Modells für die berufliche Bildung sowie dessen Bedeutung für die berufliche Lehrer:innenbildung.

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

Depicting the confrontation with anomalous data in Models of Data - Pollmeier, Pascal; Fechner, Sabine (15th Conference of The European Science Education Research Association (ESERA))
Keywords: Daten; anomale Daten; Auswertung; Umgang mit Daten; Experiment

Digitale Messwerterfassung im Chemieunterricht – Einblicke in die Entwicklung von Lernumgebungen und digitale Netzwerke - Fechner, Sabine; Stroop, Dietlinde; Ponath, Jonas; Pollmeier, Pascal (Herbsttagung des Deutscher Verein zur Förderung des mathematischen und naturwissenschaftlichen Unterrichts (MNU))
Keywords: Digital; Digitalisierung; Messsensoren; Lehrkräfte; Chemie; Nachhaltigkeit; Bildung für nachhaltige Entwicklung; BNE

Abschlussbericht zum Forschungsprojekt ‚Gelingensbedingungen und Transfer von erfolgreichen Digitalisierungsprozessen an Schulen in Nordrhein-Westfalen (GuTe DigiSchulen NRW) - Gerick, J.; Eickelmann, Birgit; Panten, B.; Rothärmel, A.; Rau, M.; Gottschalk, T.

Felix Tacke, Sprachliche Aufmerksamkeitslenkung. Historische Syntax und Pragmatik romanischer Zeigeaktkonstruktionen, Frankfurt am Main (Vittorio Klostermann) 2022, xiii + 616 p. (Analecta Romanica 92) - Kunert, Irene Dorothea (Vox Romanica)

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Does augmented reality help to understand chemical phenomena during hands-on experiments?–Implications for cognitive load and learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Tunable vector beam decoder by inverse design for high-dimensional quantum key distribution with 3D polarized spatial modes
Spatial modes of light have become highly attractive to increase the dimension and, thereby, security and information capacity in quantum key distribution (QKD). So far, only transverse electric field components have been considered, while longitudinal polarization components have remained neglected. Here, we present an approach to include all three spatial dimensions of electric field oscillation in QKD by implementing our tunable, on-a-chip vector beam decoder (VBD). This inversely designed device pioneers the "preparation" and "measurement" of three-dimensionally polarized mutually unbiased basis states for high-dimensional (HD) QKD and paves the way for the integration of HD QKD with spatial modes in multifunctional on-a-chip photonics platforms.

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Graft: Efficient Inference Serving for Hybrid Deep Learning With SLO Guarantees via DNN Re-Alignment - Wu, Jing; Wang, Lin; Jin, Qirui; Liu, Fangming (IEEE Transactions on Parallel and Distributed Systems)

Making use of analogical transfer in context-based learning - Wedekind, Lisa; Pollmeier, Pascal; Fechner, Sabine (15th Conference of the European Science Education Research Association (ESERA 2023))

Evidence based practice of pre-service teachers - Pollmeier, Pascal; Vogelsang, Christoph; Fechner, Sabine (15th Conference of the European Science Education Research Association (ESERA))
Keywords: Epistemologie; Evidenzen; Daten; Umgang mit Daten; Kompetenzen; Studierende; pre-service teachers